Implementación de las NIIF en el GAD municipal del cantón Echeandía en el año 2017 - Vega Rosero, Daniela Fernanda (2017)
It is established that at present all dependencies of the State must work with the system of International Financial Reporting Standards, which is why it is necessary to establish a methodological proposal, with the implementation of IFRS in the Municipal GAD Of canton Echeandía in 2017. For this purpose, the investigation of the present project was carried out after obtaining the results of the surveys and dialogues with the staff of the Financial Management of the GAD, in proposing a series of actions of relation for the implementation for to make the changes that currently demand the Ministry of Economy and Finance. For the development of the project, we have started from the problem in the Municipal GAD of canton Echeandía, which has not been implemented until now, and we have collected information from the representatives, which is a latent problem in this Institution. Thus, for the development of this work, we first focus on making a methodological proposal that will help in some way to achieve the implementation of IFRS in the Municipal GAD of canton Echeandía, which consists of a series of steps that are should do before adopting. For which we sought information that fed the present practical research work with the help of bibliographic documents such as books, brochures, which served to feed the present work. So we started with the issue, formulation of the problem, justification and the same objectives that led us to the realization of a methodological design for the implementation of the IFRS, which will serve as a contribution so that at the end of this fiscal year can adopt. , In a suggestive manner, the International Financial Reporting Standards in the Decentralized Autonomous Government, under study.